FDI, human capital and economic growth: evidence from Nigeria - Aminu, Abubakar Mikailu; Mhd Bani, Nor Yasmin (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This paper investigates the impact of foreign direct investment (FDI) and human capital on economic growth in Nigeria. The study utilizes the Autoregressive Distributed Lag (ARDL) model of cointegration covering the period 1975 to 2014. The findings reveal that FDI and human capital have no direct effect on the growth of the Nigerian economy over the sampled period in the long-run. However, when we interact FDI and human capital, the effect is positive and significant. This suggests that in Nigeria, human capital would positively encourage FDI and that taken together; it would significantly and positively impact the economic growth of the country. The findings suggest that in order to boost output through FDI, Nigeria would need to improve the educational situation in the country by increasing the level of funding especially in the research, development and innovations.